Validation of Fingernail Fluoride Concentration as a Predictor of Risk for Dental Fluorosis - Buzalaf, M. A. R.; Massaro, C. S.; Rodrigues, M. H. C.; Fukushima, R.; Pessan, Juliano Pelim [UNESP]; Whitford, G. M.; Sampaio, F. C. (Karger, 2012)
The aim of this study was to validate the use of fingernail fluoride concentrations at ages 2-7 years as predictors of the risk for developing dental fluorosis in the permanent dentition. Fifty-six children of both genders (10-15 years of age) had their incisors and premolars examined for dental fluorosis using the Thylstrup-Fejerskov index. Fingernail fluoride concentrations were obtained from previous studies when children were 2-7 years of age. Data were analyzed by unpaired t test, ANOVA, and Fisher's exact test when the fingernail fluoride concentrations were dichotomized (<= 2 or > 2 mu g/g). Children with dental fluorosis had significantly higher fingernail fluoride concentrations than those without the condition, and the concentrations tended to increase with the severity of fluorosis (r(2) = 0.47, p < 0.0001). Using a fingernail fluoride concentration of 2 mu g/g at ages 2-7 years as a threshold, this biomarker had high sensitivity (0.84) and moderate specificity (0.53) as a predictor for dental fluorosis. The high positive predictive value indicates that fingernail fluoride concentrations should be useful in public health research, since it has the potential to identify around 80% of children at risk of developing dental fluorosis. Copyright (C) 2012 S. Karger AG, Basel
Keywords: Biomarker; Dental fluorosis; Fingernail; Fluoride